Answer:
False
Step-by-step explanation:
They don't look alike
<h3>
Answer: x = (
y-2)^2 +
5</h3>
In other words, y-2 goes in the first box and 5 goes in the second box.
=================================================
Work Shown:
y^2 - 4y - x + 9 = 0
y^2 - 4y + 9 = x
x = y^2 - 4y + 9
x = y^2 - 4y + 4 + 5 .... rewrite 9 as 4+5
x = (y^2-4y+4) + 5
x = (y-2)^2 + 5 .... apply the perfect square factoring rule
So we'll have y-2 go in the first box and 5 goes in the second box
note: One version of the perfect square factoring rule says (a-b)^2 = a^2-2ab+b^2.
Answer:
x = 21.8°
Step-by-step explanation:
tan = opposite / adjacent
tan x = 8/20
tan^-1 = 21.8°
<span>Two algebraic expressions are said to be equivalent if their values obtained by substituting the values of the variables are same.</span>
Answer: 6.48
Step-by-step explanation:
Mean is 79.4, population size is 5
MAD formular is addition of variance point /population size
n∑∣xi−xˉ∣